2021
DOI: 10.1021/acs.biomac.1c01187
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Mediated Cryopreservation of Bacteriophages

Abstract: Bacteriophages (phages, bacteria-specific viruses) have biotechnological and therapeutic potential. To apply phages as pure or heterogeneous mixtures, it is essential to have a robust mechanism for transport and storage, with different phages having very different stability profiles across storage conditions. For many biologics, cryopreservation is employed for long-term storage and cryoprotectants are essential to mitigate cold-induced damage. Here, we report that poly(ethylene glycol) can be used to protect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…The size of the ice crystal formed in each solution was quantitatively analyzed by the dose-dependent curve of IRI activity, where the MLGS of ice crystals formed in PBS was assigned to a value of 100%. , The IRI activity was compared as a function of A/K composition (Figure c) and molecular weight (Figure d) of the PAK. The curves indicated that the IRI activities of the all polymers were very low at concentrations <0.01 mg/mL with a MLGS >70% of that of PBS.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The size of the ice crystal formed in each solution was quantitatively analyzed by the dose-dependent curve of IRI activity, where the MLGS of ice crystals formed in PBS was assigned to a value of 100%. , The IRI activity was compared as a function of A/K composition (Figure c) and molecular weight (Figure d) of the PAK. The curves indicated that the IRI activities of the all polymers were very low at concentrations <0.01 mg/mL with a MLGS >70% of that of PBS.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Thus, delivery of the active viruses depends on the cold chain, a distribution network designed to maintain optimally low temperatures during transportation and storage. Several agents, such as metal ions, albumin, gelatin, and poly(ethylene glycol), have been used to increase the resistance of the viruses to low temperatures [ 105 , 106 , 107 ]. However, these compounds are characterized by low cryoprotection efficiency or high cellular toxicity.…”
Section: Applications Of Aptamersmentioning
confidence: 99%
“…In this situation, polymeric materials have the advantage of filling volume that would otherwise be ice without exerting significant osmotic pressure across the cell membrane because of their high molecular weight. Some polymeric cryoprotectants, most notably poly­(vinyl alcohol) (PVA), inhibit the Ostwald ripening of ice, which is believed to impart mechanical stresses on cells during thawing. Other polymers with little to no effect on Ostwald ripening have also been employed as cryoprotectants. For example, hydroxyethyl starch, , poly­(glycerol monomethacrylate)- b -poly­(2-hydroxypropyl methacrylate), and polyvinylpyrrolidone have been used at 5–20 wt % to preserve red blood cells. Additionally, poly­(ethylene oxide) has been employed as a cryoprotectant for E. coli , alginate hydrogels have been used to encapsulate stem cells for frozen storage, and polymers with sulfoxide-appended backbones have been shown to promote superior recovery and viability in A549, 3T3, and NHDF cells …”
Section: Introductionmentioning
confidence: 99%